Electronic structures and physical properties of Mg, C, and S doped g-GaN. (August 2021) - Shen, Pengfei; Li, Enling; Zhang, Lin; Zhao, Hongyuan; Cui, Zhen; Ma, Deming
Abstract: Doping can provide hole and electron carriers into g-GaN materials to enhance conductivity and improve photoemission performance of g-GaN-based devices. In this work, we propose 9 × 9 × 1 g-GaN supercell and C, Mg, and S doped g-GaN systems (C and Mg substituting for Ga (CGa and MgGa systems), C and S substituting for N (CN and SN systems)) with different concentrations, and investigate their structural, electronic, electrical, and optical properties in the framework of first-principles calculations. N -type doping is achieved in the CGa and SN g-GaN systems, and p -type doping is achieved in the MgGa and CN g-GaN systems. C substituting for Ga is easier than C substituting for N, and the CGa g-GaN systems are more stability than the CN g-GaN systems. At the ultraviolet of the absorption spectra, the peaks of the doped g-GaN systems blue-shift or red-shift relative to the intrinsic g-GaN, and there are sharp peaks of the doped CGa and SN g-GaN systems at visible range. The work function and the carrier mobility have been modulated by doping and the electrical properties of g-GaN can be tuned effectively, which also promising significant applications in the design of 2D microelectronic devices and the integrated circuit. Highlights: The electronic structures and physical properities of intrinsic and doped g-GaN systems have been systematically explored. n -type doping is achieved in the CGa and SN g-GaN systems, and p -type doping is achieved in the MgGa and CN g-GaN systems. There are sharp absorption peaks of the CGa and SN doped g-GaN systems at visible range. The work function and the carrier mobility of g-GaN have been modulated by doping effectively.